Pengembangan Teknologi ERP Modul Accounting Management Studi Kasus PT DISS (Diamond Indo Satria Sejahtera) SAMPIT - Yuli Mariya; Mustaqiem Mustaqiem (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
ERP (Enterprise Resource Planning), which helps organizations deal with supply chains, receiving, inventory management, customer order management, production planning, shipping, accounting, human resource management, and other business functions. Accounting Management, which is closely related to the problem of presenting the information needed by an organization. Based on various forms or types of information, one of which is management accounting. ERP for Accounting Management Module is financial accounting presented in general ledger reports, trial balance and profit and loss reports. to find out the problems experienced by the problems because they still use Microsoft Excel in recording and reporting data so it takes a long time. The method in developing this system is by using the Waterfall Method. PT DISS (Diamond Indo Satria Sejahtera) is a company that sells Indosat and Mentari SIM cards as well as M-Tronik credit sales. The problems experienced include managing financial data that still uses Microsoft Excel so that it takes a long time and important documents that have been stored and not managed with the existing system so that if there is a loss or an error computer at any time, all data will be lost and it will take a long time to repeat the data management. Therefore, the system that the researcher will create is a web-based information system that functions as managing general journal financial data, trial balance and profit and loss, reporting sales data. By implementing this information system it is hoped that it can minimize errors and difficulties that have been experienced and help the finance department to search and process data quickly, precisely and without obstacles. The web-based information system uses the Waterfall method and uses the Codeigniter Framework programming language, PHP, Javascript and CSS